Pengambilan Isi Berita Online Dengan Document Object Model Berbasis PHP Untuk Sumber Data Mining - M. Didik Rochmad Wahyudi (Informasi Interaktif, 2016)
The rise of online news media, making the information can be delivered very quickly, the coverage is not limited, and easily accessible from various places. Online news also very easily spread through social media or instant messenger. This resulted in an online word can spread very quickly. In addition, the online news media can also be used for the formation of a certain opinion.To see if an online news media has a certain pattern in the formation of public opinion, this can be done through the processing of data mining. Processing of data mining can be done if the data is collected quite a lot within a certain timeframe. In order for online news content can be processed by one of the data mining algorithms to see a pattern, it is necessary to capture the news content. This process will be done by using the basic concepts of the Document Object Model (DOM). DOM concepts used in this study was written in the PHP programming language. News content taken are stored in a database for further data mining process.Keyword: Web Crawling, Document Object Model, Data Mining Resource